Increasing awareness and waste management based on community participation in overcoming illegal dumping in Wahana Harapan Bekasi Housing - Raafi Widyaputra Yulianyahya; Christian Dwi Putra Widjaya; Ansadilla Niar Sitanggang; Wildan Khubi Mukhafa; Pasya Tarosyamsa; Muhamad Daffa; Vitroh Maviroh; Aulia Wafa Lutfya Maliha (Pengmasku, 2026)
The problem of garbage accumulation in residential areas is an environmental issue that has a direct impact on the health, comfort, and quality of life of the community. One of the problems that occurs is the practice of illegal dumping which causes the accumulation of waste in residential environments and reduces the quality of the surrounding environment. This community service activity aims to increase community participation and provide education about sustainable waste management in Wahana Harapan Housing, Bekasi. The methods used are a participatory approach through field observation, interviews and surveys of 25 respondents, documentation of environmental conditions, as well as the implementation of education and socialization regarding waste sorting and the negative impact of illegal waste disposal. The results of the observation showed that the study location experienced a build-up of waste dominated by household waste and mixed waste that was suspected to come from outside. The survey results showed that 96% of respondents stated that the source of waste came from outside the area, while 88% of respondents felt that daily activities were disrupted due to the accumulation of waste. In addition, 72% of respondents considered that the government's efforts in dealing with the waste problem have not been effective, and 84% of respondents stated that the community's efforts that have been made have not had a significant impact. Educational activities show good community enthusiasm and increase understanding of the importance of waste management based on community participation. This activity produced outputs in the form of public perception data, documentation of environmental conditions, educational materials, and recommendations to strengthen the role of the community through the formation of a cleanliness management team and optimization of the waste bank program. Collaboration between the community and the government is needed to realize a more effective and sustainable waste management system.